1998
DOI: 10.1074/jbc.273.27.16694
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Creatine Kinase Is a Prime Target of Peroxynitrite-induced Modification and Inactivation

Abstract: The reaction of peroxynitrite (PN) with sarcomeric mitochondrial creatine kinase (Mib-CK; EC 2.7.3.2) was observed at different stages of complexity (i) with purified Mi-CK, (ii) with enzyme bound on isolated mitoplasts, and (iii) within intact respiring mitochondria. Creatine-stimulated respiration was abolished by PN concentrations likely to be physiological and far before the respiratory chain itself was affected, thus demonstrating that Mi-CK is a prime target for inactivation by PN in intact mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
103
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 171 publications
(111 citation statements)
references
References 54 publications
8
103
0
Order By: Relevance
“…49), but concentrations of up to 500 M have also been reported Ref. 50). The rate constant for the inactivation of recombinant NAT1 by peroxynitrite was determined to be 5 ϫ 10 4 M Ϫ1 ⅐s Ϫ1 , indicating that the reaction between peroxynitrite and the enzyme is extremely fast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…49), but concentrations of up to 500 M have also been reported Ref. 50). The rate constant for the inactivation of recombinant NAT1 by peroxynitrite was determined to be 5 ϫ 10 4 M Ϫ1 ⅐s Ϫ1 , indicating that the reaction between peroxynitrite and the enzyme is extremely fast.…”
Section: Discussionmentioning
confidence: 99%
“…SIN1 has been shown to attack many biological targets in the same manner as authentic peroxynitrite and, thus, has been widely used as a source of peroxynitrite in studies using purified proteins and cultured cells (47). Physiological concentrations of peroxynitrite in vivo have been estimated to be ϳ50 M (49), although 500 M concentrations have been found within phagolysosomes of activated macrophages (50).…”
Section: Peroxynitrite and Sin1-generated Peroxynitrite Inactivates Nmentioning
confidence: 99%
“…Several studies have shown that oxidative stress is associated with increased mitochondrial DNA damage, lipid peroxidation, inhibition of electron transport, and inactivation of specific mitochondrial enzymes. 13,[27][28][29][30] The mitochondrial damage associated with SHS exposure and hypercholesterolemia reported here may compromise important metabolic processes that influence both endothelial and vascular smooth muscle cell function, key components of atherogenesis. Consequently, our findings are consistent with present theories that oxidative stress mediates CVD by causing mitochondrial damage and dysfunction in tissues, which ultimately lead to compromised energetic capacities and cell dysfunction, important early events in CVD.…”
Section: Discussionmentioning
confidence: 99%
“…CKs are prime targets of oxidative damage. MtCK in particular is a principal target of such damage, not only because if its sensitivity [66,100], but also due to its mitochondrial localization. Our laboratory has shown that though there is increased expression of CK in AD, it is significantly oxidized and its activity significantly reduced [7,33].…”
Section: Glyceraldehyde-3-phosphate Dehydrogenase (Gapdh)mentioning
confidence: 99%